The beta-transformation: a case study for chaos based cryptography - Kamel Ariffin, Muhammad Rezal; Md Noorani, Mohd Salmi (Malaysian Society for Cryptology Research, 2009)
In this paper we study characteristics of the beta-transformation and its suitability as a candidate for implementation as a symmetric cryptosystem. For β > 1 the betatransformation is given by fβ (x) = βx(mod1) and x ∈ [0, 1]. It is well known that its Lyapunov exponent is λ = logβ. Since λ > 0 it ensures that the beta-transformation is a non-linear chaotic system. Finally, we will also attempt to build a discrete version of the beta-transformation.